#MeToo and modernism - Field, Robin E., 1976-; Jordan, Jerrica (Clemson University Press, 2022)
"#MeToo and Modernism opens new critical conversations about modernism and power, privilege, and patriarchy to uncover a united literary movement against sexual violence. This volume showcases how authors, whether purposely or not, challenge patriarchal viewpoints regarding sexuality, gender, and race and allowed readers different methods of interpretation for trauma narratives"--